Sphingosine 1‐Phosphate (S1P) Induces S1P2 Receptor‐Dependent Tonic Contraction in Murine Iliac Lymph Vessels. (9th January 2013) - Kimizuka, Koichiro; Kawai, Yoshiko; Maejima, Daisuke; Ajima, Kumiko; Kaidoh, Maki; Ohhashi, Toshio
Abstract Objective We studied the effects of S1P on the diameter and spontaneous contraction of murine iliac collecting lymph vessels. Methods The isolated lymph vessel was cannulated with two glass micropipettes and then pressurized to 4 cmH2O at the intraluminal pressure. The changes in lymph vessel diameter were measured using a custom‐made diameter‐detection device. Immunohistochemical studies were also performed to confirm S1P receptors on the lymph vessels. Results S1P (10−7 M) had no significant effect on the frequency or amplitude of the lymph vessels' spontaneous contractions. In contrast, S1P (10−8–10−6 M) produced a concentration‐related reduction in lymph vessel diameter (tonic contraction). Pretreatment with 10−4 M l–NAME or 10−5 M aspirin had no significant effect on the S1P‐induced tonic contraction of the lymph vessels. To evaluate the intracellular signal transduction pathway responsible for the S1P‐induced tonic contractions and their Ca2+‐dependence, we investigated the effects of JTE013, VPC23019, U‐73122, xestospongin C, and nifedipine on the S1P‐induced tonic contractions. All of these inhibitors except VPC23019 and nifedipine significantly reduced the S1P‐induced tonic contractions. S1P (5x10−7 M) also induced significant tonic contractions in the lymph vessels that had been superfused with high K+ Krebs‐bicarbonate solution or Ca2+‐free high K+ Krebs solution containing 1 mM EGTA. S1P2 receptors were immunohistochemically detected in the lymph vessels. Conclusion These findings suggest that neither endogenous NO nor prostaglandins are involved in the S1P‐induced tonic contraction of lymph vessels, which is mainly caused by Ca2+ release from intracellular Ca2+ stores through the activation of S1P2 and 1, 4, 5 IP3 receptors.